Symposium 1: The Space Occupied by Networked Learning in the Higher Education Curriculum: Revisiting the Networked Learning Manifesto: Symposium Introduction - Hodgson, Vivien; Beaty, Liz; Cousin, Glynis (Proceedings of the International Conference on Networked Learning, 2010)
At Networked Learning 2002 following an ESRC seminar series a group of us presented a manifesto entitled: Working towards E-Quality in Networked e-Learning in Higher Education: A Manifesto Statement for Debate. (Sheffield 2002). The manifesto was and is a rhetorical document – such is the nature of manifestos. The intention of this symposium is to explore the theoretical and empirical substance of the claims therein and to consider their currency eight years on. Since 2002 there has been a great deal of development both in technological and pedagogical innovation and in the integration between the two. We feel it is timely to review the Manifesto to look at what might be missing and to consider what new issues have emerged and how the field of NL has developed. One of the intentions of the Manifesto was to claim a space for radical pedagogies within technology supported and on-line learning. The Manifesto’s focus on learning communities, the social and interactive aspects of learning and the significance of technology for the co-construction of knowledge was an initial attempt to do this. It succeeded in capturing some of the emergent ideas of the pedagogical potential considered of critical importance today. The Manifesto covered five key themes :– 1. a working definition of networked e-learning; 2. learning, teaching and assessment; 3. changing the relationship between teachers and learners; 4. supporting democratic processes, diversity and inclusion; 5. the need for a networked e-learning policy. The symposium plan is to address each of these themes at the conference and then run an online seminar post conference to discuss further the issues and questions raised during the symposium session. At the symposium we will present a set of related papers comprising an introductory overview paper, which will discuss themes 1 and 5, and three thematic papers looking in depth at aspects of themes 2, 3 and 4. The four papers are; Paper 1: Revisiting the E-Quality in Networked Learning Manifesto Liz Beaty, Glynis Cousin and Vivien Hodgson This paper will re-introduce the original manifesto presented at the Networked Learning conference in 2002. It will then focus on two themes; the working definition of networked learning, arguing that it is no longer necessary or helpful to include the ‘e’ in networked e-learning. The other theme this paper focuses on is the need for a networked learning policy based on explicit educational values and theory. Paper 2; Learning, Teaching and Assessment in Networked Learning Vivien Hodgson and Michael Reynolds This paper examines the ideas behind the statements made in the Manifesto about learning, teaching and assessment in networked learning and the meaning and relevance of some of the key ideas to the current theory and practice of networked learning. The paper reviews current thinking in order to highlight issues which the manifesto raises and in addition, to examine these issues from the perspective of an empirical research study of networked learning practice. Paper 3; Re-Conceptualising the Boundaries of Networked Learning: The shifting relationship between learners and teachers Liz Beaty and James Howard This paper engages with the changing relationship between teachers and learners. The paper argues that the ideas contained within the Manifesto can be advanced to more fully capture the shifting roles and relationships inherent within networked learning. To this end, this paper focuses on a core set of boundary definitions, central to the way networked learning is conceptualised and experienced. The paper revisits the concept of expertise within learning and argues for a new understanding of the role of expertise defined by transient boundaries. Expertise becoming a quality that moves between members of learning networks, dependent upon time, activity and focus. The consequences of this for professional development are explored. Paper 4; Student Led Network Learning Design. Glynis Cousin and Paul Brett The theme examined by this paper is the one of supporting democratic processes, diversity and inclusion. In the paper the need to be apace with the ways in which the present generation of students are constituted as learners through technology is argued, together with the requirement to acknowledge the distinctiveness of this generation. The paper suggests that technical expertise and novel modes of learning are characteristic of this generation and cnsquently offer radical possibilities for network learning to soften the power of teachers and to position students as co-producers of knowledge. A framework for learning in the 21st Century The intention is that each paper will identify key questions raised by each of the areas covered in the original Manifesto. The overall question that we would like to ask is; Have we reached a point where we require a framework for learning in the 21st Century rather than a revised version of the 2002 E-Quality in Networked e-learning in Higher Education Manifesto?